2016
DOI: 10.1111/hel.12313
|View full text |Cite
|
Sign up to set email alerts
|

Rabeprazole, Minocycline, Amoxicillin, and Bismuth as First‐Line and Second‐Line Regimens for Helicobacter pylori Eradication

Abstract: The eradication efficacies of RMAB therapy as first-line and second-line regimens were satisfactory with good compliance and safety in a region with high antibiotic resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(69 citation statements)
references
References 31 publications
1
63
0
Order By: Relevance
“…Educational levels were categorized by years of education (< 7, 7-9, 10-12, 13-16, or > 16 years). Poor adherence to H. pylori treatment was defined as patient reporting < 80% adherence of prescribed therapy[ 22 ]. Severe adverse event was defined as treatment-related adverse event necessitating discontinuation of therapy within 10 d.…”
Section: Methodsmentioning
confidence: 99%
“…Educational levels were categorized by years of education (< 7, 7-9, 10-12, 13-16, or > 16 years). Poor adherence to H. pylori treatment was defined as patient reporting < 80% adherence of prescribed therapy[ 22 ]. Severe adverse event was defined as treatment-related adverse event necessitating discontinuation of therapy within 10 d.…”
Section: Methodsmentioning
confidence: 99%
“…The rabeprazole group had eradication rates of 87.5% in first-line therapy and 82.9% for second-line. 58 The group receiving esomeprazole reported 85.5% eradication rates in first-line therapy and 82.8% for second-line. 59 A study from Croatia reported eradication rates of 80.64% for bismuth quadruple therapy with pantoprazole, metronidazole, and moxifloxacin.…”
Section: Bismuth-based Therapymentioning
confidence: 98%
“…A group from China reported two separate prospective studies from a region with high antibiotic resistance rates looking at bismuth‐based quadruple therapy for 14 days with minocycline, amoxicillin, and in one case rabeprazole and the other esomeprazole. The rabeprazole group had eradication rates of 87.5% in first‐line therapy and 82.9% for second‐line . The group receiving esomeprazole reported 85.5% eradication rates in first‐line therapy and 82.8% for second‐line .…”
Section: Bismuth‐based Therapymentioning
confidence: 99%
“…Support for the use of doxycycline in H. pylori eradication regimens was found in a meta‐analysis carried out this year which showed a pooled OR for eradication success rate of 1.292 . Another study looked at rabeprazole, minocycline, bismuth, and amoxicillin as both first‐ and second‐line treatment, finding eradication rates of 87.5% and 82.9%, respectively . A novel and very interesting study from Turkey looked at using bismuth as part of a 5‐day, 5‐drug concomitant regime with omeprazole, clarithromycin, amoxicillin, and metronidazole as a first‐line treatment and found excellent tolerability and efficacy with compliance rate of 97.3% and eradication at 93.1% .…”
Section: Bismuth Therapymentioning
confidence: 99%
“…51 Another study looked at rabeprazole, minocycline, bismuth, and amoxicillin as both first-and second-line treatment, finding eradication rates of 87.5% and 82.9%, respectively. 52 The anti-H. pylori mechanism of bismuth is not fully understood, but one mechanistic study carried out this year suggests it works by impeding proton entry into the bacteria, leading to a decrease in the expected fall in cytoplasmic pH. 56 With cytoplasmic pH remaining within range for increased metabolic activity of a neutralophil, the efficacy of growth-dependent antibiotics was augmented.…”
Section: Bismuth Therapymentioning
confidence: 99%